2016
DOI: 10.1016/j.vetpar.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Implications of between-isolate variation for climate change impact modelling of Haemonchus contortus populations

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…However, none have explored the potential for resistance to mitigate climate-driven increases in infection pressure. The simulations presented in this study, under the assumption of equal FEC input, no parasite adaptation to a changing climate (Rose Vineer et al, 2016), and the modest decrease in FECs observed in low EBV compared with high EBV ewes, predicted that pasture infectivity could be reduced to historic levels by introducing resistant ewes.…”
Section: Discussionmentioning
confidence: 91%
“…However, none have explored the potential for resistance to mitigate climate-driven increases in infection pressure. The simulations presented in this study, under the assumption of equal FEC input, no parasite adaptation to a changing climate (Rose Vineer et al, 2016), and the modest decrease in FECs observed in low EBV compared with high EBV ewes, predicted that pasture infectivity could be reduced to historic levels by introducing resistant ewes.…”
Section: Discussionmentioning
confidence: 91%
“…west coast 2 . The impact of these changes on egg maturation and hatching, larval development and subsequent epidemiology of gastro‐intestinal nematode infections is difficult to accurately predict but there have been well‐documented changes in prevalence, seasonality and geographic spread of livestock pathogens in recent years 3–7 …”
Section: Introductionmentioning
confidence: 99%
“…AHR is difficult to detect in herds because it is caused by an increase in the frequency of resistance alleles through the selection imposed by the repeated use of a given AH (FLEMING et al, 2006). Sheep are hosts to a wide variety of gastrointestinal nematodes that cause clinical symptoms depending on the prevalence of each species, which varies as a function of climate and herd management system (ROSE VINEER et al, 2016). The most prevalent nematodes in most of Brazil are Haemonchus spp., Trichostrongylus spp., Cooperia spp., Oesophagostomum spp.…”
Section: Introductionmentioning
confidence: 99%